Admitted Ocular Emergencies: A Four Year Review - Naeem Khan, Salim Khan, Shad Muhammad, Arshad Iqbal, Snaullah Jan, Muhammad (Pakistan Journal of Ophthalmology, 2007)
Purpose: To acquaint the ophthalmologists and related health professionals about the magnitude of admitted ocular emergencies (OE) for better prevention and management. Material and Methods: This study was conducted over a period of 4 years from 1st January 2000 to 31st December 2003 at the Department of Ophthalmology, Khyber Institute of Ophthalmic Medical Sciences, Lady Reading Hospital, Peshawar, Pakistan. A comprehensive review of the computer record available for admitted ocular emergencies was carried out. Results: Total admissions during the study period were 13807. Total admitted ocular emergencies (OE) were 2789 i.e 20.2% of the total admission. Male to female ratio was 2:1. Non-traumatic OE were 53.0% while traumatic OE were 47.0%. In non-traumatic group males were 59.9% while females were 40.1%. In traumatic group males were 74.2% and females were 25.8%. In non-traumatic group almost 2/3 of the patients were of 40 years and above age group while in traumatic group more than half of the patients were less than 20 years of age. Corneal ulcers (39.8%) and acute glaucomas (23.3%) were the leading causes of the non-traumatic group while open globe injuries (OGI) (71.9%) were leading the list of traumatic OE. Total surgical procedures performed for ocular emergencies were 1988 i.e 16.0% of the total major ophthalmic surgeries. Average stay in the hospital for non-traumatic OE was 6.6 days, whereas, for the traumatic OE was 5.5 days. Conclusions: OE formed significant proportion of total ophthalmic admissions. Traumatic OE were almost equal to non-traumatic OE. Male were affected more commonly specially in traumatic group. Average hospital stay for OE was longer than routine admissions. Most of OE needed surgical intervention for proper management.